Paleoproterozoic Pt-Pd Fedorovo-Pansky and Cu-Ni-Cr Monchegorsk Ore Complexes: Age, Metamorphism, and Crustal Contamination According to Sm-Nd Data - Pavel A. Serov (Minerals, 2021)
This paper continues the Sm-Nd isotope geochronological research carried out at the two largest Paleoproterozoic ore complexes of the northeastern Baltic Shield, i.e., the Cu-Ni-Cr Monchegorsk and the Pt-Pd Fedorovo-Pansky intrusions. These economically significant deposits are examples of layered complexes in the northeastern part of the Fennoscandian Shield. Understanding the stages of their formation and transformation helps in the reconstruction of the long-term evolution of ore-forming systems. This knowledge is necessary for subsequent critical metallogenic and geodynamic conclusions. We applied the Sm-Nd method of comprehensive age determination to define the main age ranges of intrusion. Syngenetic ore genesis occurred 2.53–2.85 Ga; hydrothermal metasomatic ore formation took place 2.70 Ga; and the injection of additional magma batches occurred 2.44–2.50 Ga. The rock transformation and redeposited ore formation at 2.0–1.9 Ga corresponded to the beginning of the Svecofennian events, widely presented on the Fennoscandian Shield. According to geochronological and Nd-Sr isotope data, rocks of the Monchegorsk and the Fedorovo-Pansky complexes seemed to have an anomalous mantle source in common with Paleoproterozoic layered intrusions of the Fennoscandian Shield (enriched with lithophile elements, εNd values vary from −3.0 to +2.5 and ISr 0.702–0.705). The data obtained comply with the known isotope-geochemical and geochronological characteristics of ore-bearing layered intrusions in the northeastern Baltic Shield. An interaction model of parental melts of the Fennoscandian layered intrusions and crustal matter shows a small level of contamination within the usual range of 5–10%. However, the margins of the Monchetundra massif indicate a much higher level of crustal contamination caused by active interaction of parental magmas and host rock.